A Systematic Review of Fault Detection and Diagnosis Methods for Induction Motors - Maciejewski, Narco Afonso Ravazzoli; Treml, Aline Elly; Flauzino, Rogerio Andrade (2020 FORTEI-International Conference on Electrical Engineering (FORTEI-ICEE), 2020)
Induction motors are the main elements for converting electrical energy into mechanics for the productive sector since their low cost and long durability include their most attractive characteristics. Also, the need to reduce maintenance costs and the implementation of predictive techniques, aiming to minimize setbacks generated by unexpected disconnections of production lines, becomes essential and a great incentive for the development of systems capable of identifying faults. Given this, this paper implements a systematic search to identify papers and other scientific and technological papers to reach state of the art and the technique of the theme of monitoring faults in induction motors. With this, the primary methods that have been used for this purpose were identified, and in this way, it is possible to suggest new lines of research on the subject of detection and diagnose faults in induction motors.